Marketing Strategy for “Kampung Wisata Bunga” Ornamental Plants Based on Local Potential (Universitas Dr. Soetomo, 2022)
Gresik Regency is one of the regencies in East Java, which has quite some tourist sites which are also frequently visited by local tourists, as well as from foreign countries, including Sunan Giri and Malik Ibrahim Religious tours. Although Gresik City is famous for its industrial city, on the other hand, in the southern region, it is located in Miru Hamlet and Pendem Hamlet which is located in Banyu Urip Village, Kedamean District, which has the largest ornamental plants and has wide-open export market potential. The objectives of this study are (1) Mapping of Marketing Models (Product, Price, Promotion Place) which has been carried out by ornamental plant SMEs, based on local potential in Banyu Urip Village. (2) Develop a Marketing Strategy Model for Ornamental Plants, for Business Actors “Kampung Wisata Bunga” based on local potential, Banyu Urip Village, Kab. Gresik. The research method used is qualitative, nominal data type, data analysis using SWOT analysis. The results of the study found that based on the table analysis of internal factors and external factors, the strength (S) factor had a score of 2.20 and the weakness (W) had a score of 0.65. While the opportunity factor (O) has a score of 1.72 and the threat factor (T) has a score of 1.33. So that the IFAS score is 2.84 and the EFAS score is 3.05. So the strategies used are (1) Aggressive Strategy, (2) Diversification Strategy, (3) Turnaround Strategy, (4) Defensive Strategy. Keywords: SWOT Strategy, Flower Tourism Village, Local Potential